2010
DOI: 10.1590/s0100-69912010000400004
|View full text |Cite
|
Sign up to set email alerts
|

Cisto mesentérico: aspectos clínicos e anátomopatológicos

Abstract: The mesenteric cysts presented clinically with unspecific symptoms. CTscan was more effective than ultrasonography for the diagnosis. Lymphangiomas and mesothelioma had been found in equal ratios. The complete resection of the cyst was the treatment of election. There were no deaths in postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 24 publications
0
30
0
11
Order By: Relevance
“…There are no pathognomonic signs and symptoms of mesenteric cyst; However, paper presented by Santana et al 11 reporting 18 cases showed abdominal pain and mass (72%), vomiting and constipation; one patient presented with acute abdomen pain. Palpation usually presents itself painless, smooth contour and well defined with mobility in the transverse direction and around its axis (Tillaux signal) [2][3][4][5][6][7][8][9][10][11] The increase in abdominal volume is slow, progressive and late noticed in some cases, mingling with ascites in about 18-20%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are no pathognomonic signs and symptoms of mesenteric cyst; However, paper presented by Santana et al 11 reporting 18 cases showed abdominal pain and mass (72%), vomiting and constipation; one patient presented with acute abdomen pain. Palpation usually presents itself painless, smooth contour and well defined with mobility in the transverse direction and around its axis (Tillaux signal) [2][3][4][5][6][7][8][9][10][11] The increase in abdominal volume is slow, progressive and late noticed in some cases, mingling with ascites in about 18-20%.…”
Section: Discussionmentioning
confidence: 99%
“…Palpation usually presents itself painless, smooth contour and well defined with mobility in the transverse direction and around its axis (Tillaux signal) [2][3][4][5][6][7][8][9][10][11] The increase in abdominal volume is slow, progressive and late noticed in some cases, mingling with ascites in about 18-20%. There are few reports of malignant mesenteric cysts, usually low-grade sarcomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However these studies help to determine, if the tumor is cystic, its size and location, but they are insufficient to establish an accurate preoperative diagnosis. The definitive diagnosis of lymphangioma is based on histopathology and immunochemistry [11].…”
Section: Differential Diagnosismentioning
confidence: 99%